Analysis of Technical Efficiency of USAID-MARKETS II Project Participant and Non-Participant Rice Farming Households in Ebonyi State, Nigeria - Ogechi Cordelia Nwahia; Edwin Onyeabor (Indonesian Journal of Agricultural Research, 2021)
Low level production efficiency of the Nigerian farmers have continued to be a major problem towards food security in Nigeria. The study examined the technical efficiency of USAID-MARKETS II project participant and non-participant rice farming households in Ebonyi State, Nigeria. A multi-stage sampling procedure was employed to select 491 rice farming households which comprise 239 participants, and 252 non- participants. Primary source of data were collected with the use of a structured interview questionnaire and field participation. Data were analyzed using mean, standard deviation, and percentage, Z statistic, and stochastic frontier Model. The result from the study, reveals that the USAID-MARKETS II project participants were 92% technical efficient while USAID-MARKETS II project non-participants were 91% technical efficient. The result further reveals that a significant difference exist between the participants’ technical efficiency and that of non-participants of USAID-MARKETS II project. Household size and education were the vital factors that improved technical efficiency of the rice farmers. Therefore, Ebonyi rice farmers should be adequately trained on modern rice production techniques by the government agency, Agricultural Development Programme (ADP) and non-governmental agencies. Also, adequate extension services should be provided to the farmers by the ADP for proper information dissemination.